IMPLEMENTATION OF INDEPENDENT LEARNING TO IMPROVE SELF-EFFICACY AND LEARNING MOTIVATION - S, Kamriana; Salim, Soma (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Self-efficacy plays a significant role in the success of students' learning. Successful learning is not only limited to the height mark obtained or Grade Point Average (GPA) but self-confidence to do something well is also one of the things that must be in successful learning. Hence, this study aims to know how the implementation of independent learning increases self-efficacy and learning motivation. The method used in this study is a literature review. The author searched information from various sources such as books, journals, and other scientific papers related to the context. The data were then integrated and made as a reference in writing this paper. Results and discussion show that self-efficacy and learning motivation have a positive relationship and both are equally important to be improved. The analysis of various literature shows that the implementation of independent learning can increase self-efficacy and learning motivation.